20-month-olds Use Social Categories to Make Inductive Inferences about Agents' Preferences. Issue 2 (15th March 2021) - Pronovost, Megan A.; Scott, Rose M.
ABSTRACT: Adults use social-group membership to make inductive inferences about the properties of novel individuals, and this tendency is well established by the preschool years. Recent evidence suggests that infants attend to features associated with social groups and use social-group membership to interpret an agents' actions. The current study sought to replicate and extend these findings by clarifying whether infants' responses in prior studies reflected "in the moment" influences of social-group membership or inductive inferences about agents' properties and behaviors. Specifically, we investigated whether 20-month-old infants expect members of a social group to share characteristics, even when the target agent acts alone in the absence of other group members. Our results demonstrated that infants expected two individuals to share food preferences when they belonged to the same social group, but they had no expectations about whether members of two different social groups would share food preferences. These results suggest that by 20 months of age, infants use social-group membership to make inductive inferences about the properties of novel individuals, even when that individual is acting in the absence of its group members.